Analytic survey on the challenges of Moroccan students in higher education institutions face to distance learning - Kaouni Mouna; Lakrami Fatima; Labouidya Ouidad (Institute of Advanced Engineering and Science, 2022)
This research presents an investigation of the problems faced by Moroccan higher education students after the face-to-face learning was reinstated following the COVID-19 pandemic crisis. The proposed methodology is based on an exploratory descriptive analysis through a survey that involved students from different higher education institutions and residing in various regions of Morocco. The collected results revealed that students face pedagogical, technical and organizational constraints that prevent them from making a successful transition to distance learning, even if only partially. Indeed, many students are not motivated by the use of information and communication technology (ICT). The study finally provides recommendations for understanding and overcoming these problems.